2005
DOI: 10.1007/s10745-005-5156-z
|View full text |Cite
|
Sign up to set email alerts
|

Fire, People and Pixels: Linking Social Science and Remote Sensing to Understand Underlying Causes and Impacts of Fires in Indonesia

Abstract: This study in the wake of 1990s fire catastrophes identifies and analyzes underlying causes of vegetation fires in eight locations across Borneo and Sumatra. Multidisciplinary and multiscale analysis integrates geospatial technologies with varied social research approaches and participatory mapping. It helps fill a void of site-specific evidence on diverse underlying causes of the Indonesian fires, despite emerging consensus on macrolevel causes and impacts, and policy debates on preventing future fire disaste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
167
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 181 publications
(175 citation statements)
references
References 25 publications
3
167
0
5
Order By: Relevance
“…Underlying causes of fires within the boundary of oil palm concessions are, however, disputed and likely complex, and the blame for such fires does not always lie with concession management (Dennis et al 2005).…”
Section: A Driver Of Deforestation?mentioning
confidence: 99%
“…Underlying causes of fires within the boundary of oil palm concessions are, however, disputed and likely complex, and the blame for such fires does not always lie with concession management (Dennis et al 2005).…”
Section: A Driver Of Deforestation?mentioning
confidence: 99%
“…Remote sensing and social science investigations using participatory mapping conducted by a team of researchers from the Center for International Forestry Research (CIFOR), the World Agroforestry Centre (ICRAF) and the United States Forest Service (USFS), showed that both smallholders and large-scale plantations used fire as a tool, primarily for land clearing but also in specific contexts in extractive activities (Applegate et al, 2001;Dennis et al, 2004;Suyanto et al, 2002). For the first time, these social science investigations also have documented specific patterns in the use of fire as a weapon; arson arising from land disputes was shown to be an important albeit secondary factor.…”
Section: Managing Smokementioning
confidence: 99%
“…It is encouraging that the CIFOR-ICRAF-USFS research on underlying causes has begun to discern meaningful patterns in the shape and extent of remotely sensed burn scars and to relate those burn scars to the underlying causes and broader environmental and social context documented in the social science studies (Dennis et al, 2004). This holds promise as a cheap and replicable tool for future fire forensic investigations, but it is not yet possible to attribute shares of the smoke problem between smallholders and large operators or arising from purposive burning (for land clearing, resource extraction, or arson) and accidents on the scale of large areas, such as Sumatra and Borneo.…”
Section: Managing Smokementioning
confidence: 99%
See 2 more Smart Citations